Texture Dirac Mass Matrices and Lepton Asymmetry in the Minimal Seesaw Model with Tri-Bimaximal Mixing - Agus Purwanto; Bintoro Anang Subagyo; Erika Rani (Jurnal Fisika dan Aplikasinya, 2014)
We examined the minimal seesaw mechanism of 3 × 2 Dirac matrix by starting our analysis with the masses of light neutrinos with tri/bi-maximal mixing in the basis where the charged-lepton Yukawa matrix and heavy Majorana neutrino mass matrix are diagonal. We found all possible Dirac mass textures which contain one zeroentry or two in the matrix.